PENGARUH KONTAK BAHASA MASYARAKAT DESA MAJALAYA DENGAN PENDATANG DAN PENZIARAH TERHADAP CAMPUR KODE - Via Nugraha (STKIP Siliwangi, 2015)
Language constitutes man communication device to get interaction and givesinformation. Pilgrimage place that often been visitted by a lot of person of differentregions, giving influence that greatly its happening language variation. Thereforethis research intent to look for whatever variation tofu that emerging deep societieslingual contact silvan Majalaya to mix code. After analysis language varietytherefore will descry to be clear lingual mixing form that is utilized. We thatanalyzing can part of speech that experience code mixture. After analyzing forms tomix code in lingual contact among local society with immigrant and visitor,therefore we can see how big immigrant influence and visitor to mix code and deeplingual contact. Key words : Lingual contact, Code mingling, Visitor